2018
DOI: 10.3169/mta.6.18
|View full text |Cite
|
Sign up to set email alerts
|

[Invited Paper] Content Scheduling and Adaptation for Networked and Context-Aware Digital Signage: A Literature Survey

Abstract: Digital signage (DS) is becoming well accepted as a ubiquitous medium that can deliver and display various types of information by specifying the location and time. In this paper, we put our focus on the following two directions of DS development: (1) Networked DS: networking displays to form a large-scale open DS network that allows content providers to submit contents, and schedule, deliver, and display the contents at the right place and time, (2) Context-aware DS: displaying contents appropriate to the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…(1) a study of prior literature including: (a) those reported in Section 2.2, (b) a recent survey of content scheduling [86], and (c) prior requirements elicitation initiatives [8,83], (2) use cases for future display networks [22,26], and, (3) experiences of operating the world's largest research testbed for display networks [35].…”
Section: Requirements For Scheduling In Pervasive Display Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…(1) a study of prior literature including: (a) those reported in Section 2.2, (b) a recent survey of content scheduling [86], and (c) prior requirements elicitation initiatives [8,83], (2) use cases for future display networks [22,26], and, (3) experiences of operating the world's largest research testbed for display networks [35].…”
Section: Requirements For Scheduling In Pervasive Display Systemsmentioning
confidence: 99%
“…all files in a directory), no criteria is used to reduce the available content down to a smaller subset for playback. However, it is not uncommon for signage platforms to schedule based on descriptive features of the content such as format constraints (must have an audio soundtrack or portrait orientation) [86], content type (e.g. show adverts or news), media type (e.g.…”
Section: Supporting Traditional Signagementioning
confidence: 99%
See 3 more Smart Citations